MODELISASI KOTAK TISU DENGAN PENGGABUNGAN KURVA BEZIER, KURVA HERMIT DAN HASIL DEFORMASI BENDA GEOMETRI - Safitri, Dian; Juliyanto, Bagus; Ubaidillah, Firdaus (Jurusan Matematika FMIPA Universitas Jember, 2021)
The tissue box is a place to store tissues to make them look neat and protect the tissues from dirt and dust. Tissue boxes are often used in households, restaurants and also as room decorations. Therefore, the shapes of tissue boxes that are being developed are increasingly varied according to consumer interests. The tissue box consists of three main parts, namely the cover, body and base of the box. This research was carried out by developing variations in the shape of the tissue box components using the Bezier curve, the Hermit curve and the results of the deformation of geometric objects. The deformation techniques used are rotation, dilation, and curve interpolation. Tissue box modeling processes are divided into four stages. The first, modeling the tissue box by dividing into three models, namely model A, model B and model C. The second, determining the size of the tissue box components based on the model. The third, modeling tissue box components. Finally, visualizing the results of the tissue box model by combining the components so that a variety of tissue box models are produced.